Wave-piercing catamaran transom stern ventilation process. Issue 2 (3rd May 2016) - Haase, M.; Binns, J.; Thomas, G.; Bose, N.
Abstract : The new class of highly fuel-efficient medium-speed catamarans operate at speeds where the transom is partially or fully ventilated, hence it is important to understand the characteristics of the wake for resistance prediction. Unsteady Reynolds-Averaged Navier Stokes simulations were used to simulate the flow around a 98 m catamaran, at both model and full scale, and compared to model test results for a 1:22 scale model. A non-shedding squashed horseshoe vortex was found to build up in the stagnant zone past the vessel, with the transom running dry at transom draft Froude numbers of 2.5 in model test experiments and at transom draft Froude numbers of 2.4 in numerical simulations. For full-scale Reynolds numbers, ventilation occurred at transom draft Froude numbers of 2.2. Finally, unsteady Reynolds-Averaged Navier Stokes simulations are capable of accurately predicting the recirculating flow in the wake of the vessel and the state of transom ventilation.